BATAS PENGARUH BAGIAN WILAYAH KOTA (BWK) PUSAT KOTA TOMOHON TERHADAP WILAYAH SEKITARNYA - Aunike Hihola; Esry H. Laoh; Caroline B.D. Pakasi (COCOS, 2016)
ABSTRACTThis study aimed to analyze the effect of Section Urban Area limits (BWK) Tomohon City Center to other districts in the region of Tomohon and influence to several other surrounding regions, namely, Sonder, South Tondano and Tombariri. This study uses data obtained BPS North Sulawesi, BPS Tomohon, Tomohon City Department of Transportation, damn Global Positioning System (GPS). The data used in this research are secondary and primary data. Variable-variables measured in this study includes the total population (people) and distance (km). In this study, the analysis used is Breaking Point. The study lasted from December to January from preparation, data collection, to preparing the results of the research report. The research location is in Tomohon.The results of this study indicate that the development BWK Tomohon City Center (Central Tomohon) has a limit of influence varies in the surrounding area. BWK Tomohon City Center (Central Tomohon) influence on Eastern Tomohon, Tomohon Barat, Sonder, South Tondano and Tombariri. Northern Territory influence on BWK TomohonTomohon City Centre (Central Tomohon), while South Tomohon same effect on the strength of BWK Tomohon City Center (Central Tomohon). Tomohon overall effect is very significant to the three surrounding area.Keywords: Tomohon City